Spatial Images of Subjective Perception of Time in a Literary Text - Nesterik, E.; Kakzhanova, F.; Issina, G.; Shelestova, T.; Tsay, Ye.; Kusmanova, G.; Pecherskikh, T. (Aesthetics media services-aesthetixms, 2017)
The analysis presented in this article is based on the hypothesis that the category of subjective perception of time or psychological time expresses different concepts and it is formed by means of different textual categories in a literary text, including those of the category of fictional space. The hypothesis, in its turn, has been put forward on the basis of the results of literary investigations of time in the study of literature, psychology and textual linguistics. The urgency and novelty of the research is conditioned by the need for a more comprehensive study of conceptual categories of text and in particular their formal aspect (the plane of expression) as well as the interest of modern linguistics in the problem of conceptualization of the world by the means of language, the specificity of the reflection of such fundamental categories as time, space, consciousness, human being in everyday consciousness and naive linguistic world-image.
Keywords: Fictional space; Fictional time; Psychological time; Spatial images; Subjective perception of time